A comparison of three methods of semi-tethered profiling in front crawl swimming: A reliability study - Keating, R.; Kennedy, R.; Nevill, A. M.; McCabe, C. (Journal of Sports Sciences, 2025)
The study compares three methods of evaluating semi-tethered performance in front crawl swimming using different velocity extraction techniques. Thirty Level 4 swimmers (17 males, 13 females) completed three protocols: Absolute (5 × 25 m, 1-9 kg for males; 1-5 kg for females), Modified (3 × 10 m, 1, 5, 9 kg for males; 1, 3, 5 kg for females) and Velocity-Restricted (device limited to 1 m/s), across three testing sessions, 7 days apart. Absolute and Modified protocols generated load-velocity (LV) and force-velocity (FV) profiles, while Velocity-Restricted produced an FV profile to determine maximal velocity (LV-V0, FV-V0), absolute and relative load/force (L0, F0, rL0, rF0) and slope (SLV, SFV). Reliability estimates for the Absolute method: ICC 0.74-0.83, CV% 2.4-9.0% for males; ICC 0.57-0.87, CV% 2.4-11.6% for females. Modified: ICC 0.51-0.85, CV% 2.8-13.7% for males; ICC 0.16-0.80, CV% 2.9-17.1% for females. Velocity-Restricted: ICC 0.50-0.84, CV% 2.6-8.5% for males; ICC 0.10-0.55, CV% 4.2-21.7% for females. FV-V0 was significantly higher than LV-V0 (p < 0.001), showing LV and FV outputs are not interchangeable. No statistical differences between Absolute and Modified protocols suggest that the latter (5 m analysis) is a more time-efficient method. Differences in reliability highlight the need for sex-specific considerations when interpreting results.